Variable laterality of corticospinal tract axons that regenerate after spinal cord injury as a result of PTEN deletion or knock-down - Willenberg, Rafer (J Comp Neurol, 2016)
Corticospinal tract (CST) axons from one hemisphere normally extend and terminate predominantly in the contralateral spinal cord. We previously showed that deleting PTEN in the sensorimotor cortex enables CST axons to regenerate after spinal cord injury and that some regenerating axons extend along the “wrong” side. Here, we characterize the degree of specificity of regrowth in terms of laterality. PTEN was selectively deleted via cortical AAV-Cre injections in neonatal PTEN-floxed mice. As adults, mice received dorsal hemisection injuries at T12 or complete crush injuries at T9. CST axons from one hemisphere were traced by unilateral BDA injections in PTEN-deleted mice with spinal cord injury and in non-injured PTEN-floxed mice that had not received AAV-Cre. In non-injured mice, 97.9 ± 0.7% of BDA-labeled axons in white matter and 88.5 ± 1.0% of BDA-labeled axons in grey matter were contralateral to the cortex of origin. In contrast, laterality of CST axons that extended past a lesion due to PTEN deletion varied across animals. In some cases, regenerated axons extended predominantly on the ipsilateral side, in other cases, axons extended predominantly contralaterally, and in others, axons were similar in numbers on both sides. Similar results were seen in analyses of cases from previous studies using shRNA-mediated PTEN knock-down. These results indicate that CST axons that extend past a lesion due to PTEN deletion or knock-down do not maintain the contralateral rule of the non-injured CST, highlighting one aspect for how resultant circuitry from regenerating axons may differ from that of the uninjured CST.